A Basic Nietzschean Model in Lieu of the Causal Maxim. - Özkurt, Tolga Esat (Philosophia, 2022)
Causal knowledge unquestionably provides useful means to describe, explain and predict both natural and daily phenomena. This article addresses whether causality as such may not be ontologically primary and looks for an alternative fundamental mechanism encapsulating the information load of the causal framework. A probabilistic process view of reality asserting the struggle of natural forces is considered along with lines quoted from Nietzsche's posthumously published notebooks and published work. Examples from scientific discoveries, in particular neurosciences, echoing his ontology are provided. Furthermore, I propose a basic number game algorithm to illustrate and model the struggle of forces leading to causal inferences for an external observer. Nietzschean dynamic ontology involving the ceaseless struggle of will-to-power units accords with the emergentist approach to causation, which has been principally employed by the scientists working under the fields of thermodynamics, quantum mechanics and complex dynamical systems.